Renewable Rigid Diamines: Efficient, Stereospecific Synthesis of High Purity Isohexide Diamines - Thiyagarajan, Shanmugam; Gootjes, Linda; Vogelzang, Willem; van Haveren, Jacco; Lutz, Martin; van Es, Daan S. (ChemSusChem, 2011)
We report an efficient three‐step strategy for synthesizing rigid, chiral isohexide diamines derived from 1,4:3,6‐dianhydrohexitols. These biobased chiral building blocks are presently the subject of several investigations (in our and several other groups) because of their application in high‐performance biobased polymers, such as polyamides and polyurethanes. Among the three possible stereo‐isomers, dideoxy‐diamino isoidide and dideoxy‐diamino isosorbide can be synthesized from isomannide and isosorbide respectively in high yield with absolute stereo control. Furthermore, by using this methodology dideoxy‐amino isomannide—a tricyclic adduct—was obtained starting from isoidide in high yield. Our improved synthetic route is a valuable advance towards meeting scale and purity demands for evaluating the properties of new biobased performance materials, which will benefit the development of these plastics. Turning up the stereo: An efficient three‐step strategy for synthesizing chiral biobased dideoxy‐diamino isoidide and dideoxy‐diamino isosorbide in high yield with absolute stereo control is described. These highly interesting chiral building blocks are presently the subject of several investigations due to their application in high‐performance biobased polymers such as polyamides and polyurethanes.